KETIKA CINTA BERTASBIH TRANSFORMASI NOVEL KE FILM - Siti Isnaniah (Universitas Gadjah Mada, 2015)
One study of ecranisation is a transformation from novel to film. One of the novels deserves to bestudied are El Shirazy’s Ketika Cinta Bertasbih (KCB) 1 and 2. The film is based on a novel, including thereception of research resources in the form of adaptations in other media. The presence of KCB novelwhich filmed later is the phenomenon of ecranisation which siphon attention from the public from allbackgrounds and ages. The differences which frequently arise in ecranisation have often caused by thedifferences in the literary system (novel) and film. The differences which frequently arise in ecranisationhave often caused by the differences in the literary system (novel) and film. The technical issues, such asmedia novel form of words and language, meanwhile the main media of film is an audio-visual (soundand picture). Therefore, it would be reasonable if the film is different from the novel. In the KCB noveland film, the differences that exist are not only technical problems, but a deliberate distinction with aspecific purpose as well. Based on the facts above, the KCB novel and film have many differences causedby the reception process through KCB novel conducted by film production (screenwriter, director, andproducer). This case is a problem which becomes question in the mind of the readers of the KCB novel.The literary reception towards KCB novel which eventually lead to the film is a creative act as a reader.